Whole-genome sequencing offers additional but limited clinical utility compared with reanalysis of whole-exome sequencing. (November 2018) - Alfares, Ahmed; Aloraini, Taghrid; subaie, Lamia Al; Alissa, Abdulelah; Qudsi, Ahmed Al; Alahmad, Ahmed; Mutairi, Fuad Al; Alswaid, Abdulrahman; Alothaim, Ali; Eyaid, Wafaa; Albalwi, Mohammed; Alturki, Saeed; et al.
Abstract Purpose Whole-exome sequencing (WES) and whole-genome sequencing (WGS) are used to diagnose genetic and inherited disorders. However, few studies comparing the detection rates of WES and WGS in clinical settings have been performed. Methods Variant call format files were generated and raw data analysis was performed in cases in which the final molecular results showed discrepancies. We classified the possible explanations for the discrepancies into three categories: the time interval between the two tests, the technical limitations of WES, and the impact of the sequencing system type. Results This cohort comprised 108 patients with negative array comparative genomic hybridization and negative or inconclusive WES results before WGS was performed. Ten (9%) patients had positive WGS results. However, after reanalysis the WGS hit rate decreased to 7% (7 cases). In four cases the variants were identified by WES but missed for different reasons. Only 3 cases (3%) were positive by WGS but completely unidentified by WES. Conclusion In this study, we showed that 30% of the positive cases identified by WGS could be identified by reanalyzing the WES raw data, and WGS achieved an only 7% higher detection rate. Therefore, until the cost of WGS approximates that of WES, reanalyzing WES raw data is recommended before performing WGS.